2012
DOI: 10.1088/1367-2630/14/1/013046
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effects in high-Tccuprate superconductors as support for the bipolaron theory of superconductivity

Abstract: We provide a unified parameter-free explanation of the observed oxygen-isotope effects on the critical temperature, the magnetic-field penetration depth and on the normal-state pseudogap for underdoped cuprate superconductors within the framework of the multi-(bi)polaron theory with strong Coulomb and Fröhlich interactions. We also quantitatively explain the measured critical temperature and the magnitude of the magnetic-field penetration depth. This paper thus represents an important support for the bipolaron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Further studies revealed the effect of isotopic replacement on many other quantities, such as the pseudogap [7], magnetic penetration depth [8], electron dynamics [9] and quasiparticle inelastic scattering [10] . This evidence motivated a variety of theoretical ideas for the pairing mechanism, such as the bipolaron theory [11], magnetically mediated SC [12,13] and valence fluctuation [14].…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Further studies revealed the effect of isotopic replacement on many other quantities, such as the pseudogap [7], magnetic penetration depth [8], electron dynamics [9] and quasiparticle inelastic scattering [10] . This evidence motivated a variety of theoretical ideas for the pairing mechanism, such as the bipolaron theory [11], magnetically mediated SC [12,13] and valence fluctuation [14].…”
mentioning
confidence: 83%
“…where J q = j J 0,j e iR j q is the Fourier transform of the coupling. The critical behavior can be seen by expanding J Γ , in (11) or (12), around M = M c . In both cases, we obtain Eq.…”
mentioning
confidence: 99%
“…In particular the doping dependent oxygen-isotope effects on the critical temperature T c and on the in-plane supercarrier mass (ref. [7][8][9][10][11][12] ), provide direct evidence for a significant EPI and bipolaronic carriers 13 in high-temperature cuprate superconductors. Angle-resolved photoemission spectra (ARPES) 14,15 provide further evidence for the strong EPI apparently with c-axis-polarised optical phonons 16 .…”
Section: Introductionmentioning
confidence: 89%
“…Depuis leur découverte par Bednorz et Muller [1], l'origine de la supraconductivité dans les supraconducteurs à haute température, notamment les cuprates, malgré des avancées [2,3] reste inconnue. La théorie BCS qui explique convenablement la supraconductivité des supraconducteurs ''conventionnels'' par une interaction attractive entre deux électrons via des phonons est mis en défaut par la supraconductivité à haute température.…”
Section: Introductionunclassified